Comparative effectiveness of nerve block strategies for preventing postherpetic neuralgia in thoracic herpes zoster: a network meta-analysis - Wensheng Lu; Shengze He; Qi Liu; Yaozu Gu; Jie Bai (Frontiers in Neurology)
BackgroundShingles is a common global disease, with the chest region being one of its most frequently affected areas. Postherpetic neuralgia (PHN) is one of the most common and debilitating complications of this disease, characterized by high incidence, prolonged duration, and treatment resistance, severely affecting patients’ daily life and quality of life. Currently, research on the prevention of PHN remains limited. Nerve block, as a promising intervention, has been widely applied in clinical pain management. However, there is still no consensus on the efficacy and safety of different nerve block techniques for the prevention of chest-related PHN, warranting further systematic evaluation and comparison.MethodsA network meta-analysis was conducted using RevMan 5.4 and Stata 18.0, analyzing data from nine studies retrieved from four English-language databases: MEDLINE, Embase, Web of Science, and the Cochrane Central Register of Controlled Trials (CENTRAL).ResultThis study included a total of 9 randomized controlled trials, involving 741 patients with chest herpes zoster and 8 different interventions. The results of the network meta-analysis indicated that the top three interventions in terms of total effective rate were: PVB: Amide local anesthetics + Methylene blue > PVB: Methylene blue > ESPB: Amide local anesthetics + Glucocorticoid. In terms of pain level, as assessed by the Visual Analogue Scale, the top three interventions were: PVB: Amide local anesthetics + Glucocorticoid > PVB: Amide local anesthetics > ESPB: Amide local anesthetics + Glucocorticoid.ConclusionThe results of this study indicate that PVB is superior to ESPB in both reducing VAS scores and improving the total effective rate. Among the interventions, PVB: Amide local anesthetics + Methylene blue demonstrated the best performance in terms of total effective rate, while PVB: Amide local anesthetics + Glucocorticoid showed the most significant effect in reducing VAS scores.Systematic review registrationhttps://www.crd.york.ac.uk/prospero/, identifier CRD42024604329.